Penurunan Scrap Bead Ban (Blister bead) Di Area Curing Pada Produk Ban Roda Empat Dengan Konsep Siklus PDCA - Hery Hamdi Azwir; Ahmad` Sofyan; Athina Sakina Ratum (President University, 2023)
PT. A Tbk. is a company engaged in tire manufacturing, conditionally based on MTO or what is called make to order and MTS or called make to stock. The company has activities in producing tires for 2-wheeled vehicles (motorcycles), 4-wheeled (passenger sedans), or more. During the last 6 months (July to December 2020), the company's productivity has experienced problems, especially in the curing area caused by quality problems where tire product defects (blister bead) occur. Blister bead is a scrap in the curing area, where the scrap is in the form of air trapped in the tire bead which causes waste in the production. To overcome this, research was conducted using the PDCA method approach. The PDCA method is a continuous improvement process. This method carries out a systematic and continuous improvement process. The PDCA method has the advantage of taking corrective action and quality improvement once the root cause has been identified. Scrap blister bead in the period July to December 2020 is 0.095%. After making improvements to several factors, scrap blister bead decreased in the period January to April 2021, namely 0.021%. The scrap decline rate reached 0.78%.